BEEF Principle to Shooting Free Throw Accuracy Based on Biomechanical Analysis - Febriani, Ayu Rizky; Hidayat, Rohman; Syafei, Muhamad; Budi, Didik Rilastiyo; Sulaiman, Sulaiman (Ilmu Olahraga, 2022)
This study aims to determine the results of shooting free throws which were analyze biomecally using kinovea software and to find out details of the angle (degrees) resulting from shooting free throw. Design of this research is descriptive quantitative with persentage by analizyng the free throw shooting motion which is 4 categorized; result of point shooting by applying the BEEF principle, shooting result point not applying the BEEF principle, shooting result no point but applying the BEEF principle, shooting result no point and no applying BEEF principle. The population are who were members of the UKM basketball Jenderal Soedirman University. The sample in this reseacrh amounted to 30 people. The analysis shooting motion the incoming ball free throw by applying the BEEF principle gets the highest percentage results, 46.6%; Balance of 83.90°, Elbow 89.21°, all off sample of this category is focused on the target shooting, follow through 179.98°. Shooting free throw by applying the correct BEEF principle will get a greater percentage of balls in than not applying. Of course with the support other dominant factors such as mental, self efficacy and antropometry.